Application of time-domain NMR as a methodology to quantify adulteration of diesel fuel with soybean oil and frying oil. (15th September 2019) - Cunha, Danyelle A.; Neto, Álvaro C.; Colnago, Luiz A.; Castro, Eustáquio V.R.; Barbosa, Lúcio L.
Highlights: NMR allowed detect and quantify the adulteration of diesel fuel with soybean oil. NMR quantified the adulteration of diesel fuel with residual oil. The samples of adulterated diesel showed high viscosity values. The time domain NMR showed be a great alternative to the Mid-infrared. Abstract: Diesel fuel is responsible for approximately 47% of all fuel consumed in road transportation in Brazil. As a result of this high consumption, fuel adulteration has increased and fraudsters have used irregular substances, such as kerosene and residual and vegetable oils, which have good miscibility with the fuel making it difficult to detect the fraud. Adulteration causes irreparable damage to engines, such as sudden failure, difficulty in starting, increased fuel consumption, low fuel spraying rate in the combustion chamber, and increased emissions of particulate matter. In this work, time domain nuclear magnetic resonance (TD-NMR) was studied as a method to detect diesel adulteration with soybean oil and frying oil. NMR has advantages over traditional techniques as it does not require sample preparation; it is non-destructive and allows rapid analyses (∼1 min). The TD-NMR analyses showed that the transverse relaxation time (T2 ) of commercial diesel sample varied between 0.65 and 0.68 s and 0.13 s for both soybean and residual oils. The transverse relaxation times of adulterated diesel samples, ranging from 5 to 100% vegetable oil, show a large T2 variation from 0.13 to 0.68 s. These values show a good determination coefficient (R 2 = 0.99) to the results obtained with medium infrared spectroscopy, which is the standard technique to determine the vegetable oil content in diesel fuel. Therefore, we concluded that TD-NMR could be a useful method to detect and quantify diesel adulteration with new and used vegetable oils.